Isolamento e identificação de fungos endofíticos de Abarema cochliocarpos (Gomes) Barneby & Grimes e Dalbergia ecastophyllum (L.) Taub., suas relações antagônicas e atividade antioxidante de seus extratos - Silva, Ricardo Manoel dos Santos (2011)
The search for new substances of pharmaceutical interest in the area or even in the most diverse agricultural industry uses, has led researchers to seek alternatives before not properly explored. One such alternative would be to isolate the microorganisms that inhabit plant asymptomatically to produce new substances, studies have shown that these microorganisms, called endophytes, through the coevolution of host plants, has given them many benefits such as protection and resistance pest attack. In parallel, it is seen that many compounds produced by host plants, can also be produced by these microorganisms, and thus its industrial production could be facilitated. This study aimed to isolate and identify fungal endophytes from two species A. cochliocarpos and D. ecsatophyllum popularly known as barbatimão and rabo – de- bugio, respectively, and to examine its antagonism between fungi isolated and the antioxidant activity are also the focus of this work. Endophytic fungi were isolated from six. Of these, five were identified as two of the genus Phomopsis fungi, a fungus of the genus Guignardia and one identified as being of order Pleosporales, the fungus was identified as the fifth genus Nigrospora. One of the fungus could not be identified by the technique used and was called DeF2. The fungi grew better when kept in dark on PDA growth medium and BSA in the laboratory. As antagonists, we observed that the isolates coming from the host D. ecstophyllum were the most efficient and that one gender may have different behaviors depending on the host that originated. From experiments with mycelia of these fungi were obtained organic extrados of different polarities, and the analysis of the antioxidant activity of these extracts showed that the fungus Phomopsis sp. isolated from D. ecastophyllum presented extracts with antioxidant activity than those of other fungi analyzed.